Capital Account Convertibility : Review of Experience and Implications for IMF Policies - Evens, Owen (Occasional Papers; Occasional Paper, 1995)
The paper summarizes the main issues arising from experiences of industrial and developing countries with capital account liberalization and it examines the IMF's treatment of capital controls in its surveillance, use of IMF resources, and technical assistance activities. Case studies of recent experiences with capital controls in Chile, Colombia, Malaysia, and Venezuela are presented.